Trinity in unity in Christian-Muslim relations : the work of the Pontifical Council for Interreligious Dialogue - Jukko, Risto. (History of Christian-Muslim relations, 2007)
Christian-Muslim relations are one of the major issues in contemporary theology of religions. This book deals with the theological foundations that have been laid for these relations in the recent official documents (1966-2005) of the Secretariat for Non-Christians/the Pontifical Council for Interreligious Dialogue. There is a continuous interrelationship in recent Roman Catholic thinking between philosophy (existentialism and personalism) and theology ("nouvelle théologie" and "kerygmatic theology"). This study shows that the doctrine of the Trinitarian nature of God is the cornerstone on which this documentation rests, and that the Trinitarian dimension of Roman Catholic theology of religions will challenge the Christology of 21st century theology.